تقييم فعالية الإيزوتريتينوئين الفموي بالجرعة الاعتيادية والمنخفضة والنبضية بعلاج العد الشائع - اسماعيل, محمد; السيد, فاخر; قاسم, بشرى (Latakia University Journal -Medical Sciences Series, 2018)
Background: Acne vulgaris is a chronic inflammatory disease, and isotretinoin is the most effective drug in the treatment of acne vulgaris. Reaching to a total cumulative dose of 120 – 150 mg/kg is known to achieve good results.Recently, there have been many studies regarding the efficacy of low-dose and intermittent isotretinoin treatment in patients with mild and moderate acne. Objective: we aimed to evaluate the clinical efficacy and tolerability of low-dose and intermittent isotretinoin regimens and compare them directly with conventional isotretinoin treatment. Methods: This study included (107) patients, who attended to the dermatology clinics at Tishreen university hospital in Lattakia during (2016 – 2017), and they were clinically diagnosed with moderate acne vulgaris. The patients were randomly divided into 3 groups: Group A: included 34 patients who received Isotretinoin at 0.5 – 0.7 mg/kg daily. Group B: included 38 patients who received Isotretinoin at 0.25 – 0.4 mg/kg daily. Group C: included 35 patients who received Isotretinoin at 0.5 – 0.7 mg/kg daily for 1 week out of every 4 weeks. The total period of drug administration was 24 weeks in the three groups. 6 months follow-up evaluation after the end of treatment was also performed. Results: We found that when considering efficacy , tolerability, patient satisfaction and relapse rate, low-dose treatment was most suitable for patients with moderate acne. مقدمة: العد الشائع هو مرض التهابي مزمن، يعتبر الإيزوتريتينوئين الدواء الأكثر فعالية بعلاجه. إن الوصول لجرعة تراكمية منه ومقدارها 120 – 150 مغ/كغ معروفة سابقاً بتحقيقها لنتائج جيدة. توجد اليوم العديد من الدراسات التي تدعم فعالية الجرعات المنخفضة والنبضية بعلاج العد الشائع الخفيف ومتوسط الشدة. الهدف: تقييم الفعالية السريرية والآثار الجانبية ومعدل النكس للجرعة المنخفضة المستمرة والجرعة النبضية من الإيزوتريتينوئين ومقارنتها مع الجرعة الاعتيادية من الايزوتريتينوئين لدى مرضى العد الشائع متوسط الشدة. طرق البحث: شملت هذه الدراسة (107) مرضى من مراجعي العيادات الجلدية بمشفى تشرين الجامعي باللاذقية خلال الفترة (2016 -2017)، والذين شخص لديهم عد شائع متوسط الشدة سريرياً. تم توزيع المرضى عشوائياً إلى ثلاث مجموعات: مجموعة A: تضمنت 34 مريضاً تلقوا جرعة مقدارها 0.5 – 0.7 مغ/كغ/اليوم من الإيزوتريتينوئين. مجموعة B: تضمنت 38 مريضاً تلقوا جرعة مقدارها 0.25 - 0.4 مغ/كغ/اليوم من الإيزوتريتينوئين. مجموعةC: تضمنت35 مريضاً تلقوا جرعة مقدارها 0.5 – 0.7 مغ/كغ/اليوم لمدة أسبوع من كل شهر من الإيزوتريتينوئين. المدة الكلية للمعالجة كانت 24 أسبوع بالمجموعات الثلاث. تم إجراء تقييم بعد ستة أشهر من المتابعة بشكل تالٍ لإيقاف العلاج. النتائج: توصلت دراستنا إلى أنه عند الأخذ بعين الاعتبار الفعالية، التحمل، ورضا المريض ومعدل النكس فإن الجرعة المنخفضة هي الجرعة الأمثل لمرضى العد الشائع متوسط الشدة.